Enhancing Preschool Teachers' Use of Pyramid Model Practices Through Coaching Intervention - Rakap, Salih; Balikci, Serife (Springer, 2025)
The social-emotional development of young children has been shown to have a significant impact on their long-term success in life. The Pyramid Model is a widely recognized framework that preschool teachers can use to support socio-emotional development. The present study investigated the effects of a professional development program, including teacher training and coaching, on preschool teachers' utilization of social-emotional teaching practices associated with the Pyramid Model. Three preschool teachers and three children participated in this study, which employed a multiple baseline across behaviors design, implemented across participants. The combined training and coaching intervention had a positive impact on all participating teachers' implementation of social-emotional teaching practices. Moreover, the study established a clear correlation between increased implementation of these practices and a gradual reduction in challenging behaviors displayed by the children. The participating teachers expressed high acceptability and perceived relevance of the professional development intervention and Pyramid Model practices. The study contributes to the existing literature on supporting social-emotional development in early childhood settings and highlights the potential of professional development interventions to enhance teacher practices. Recommendations for future research and implications for practice are discussed.
Rakap, Salih/0000-0001-7853-3825
Keywords: Social-Emotional Development; Professional Development; Coaching; Early Childhood; Pyramid Model Practices